Wetland de fluxo vertical com diferentes tipos de meio suporte para o tratamento da drenagem ácida de mina - Silva, Sthéferson Bruno da (2023)
Acid mine drainage (AMD) is an effluent generated in the exploration of minerals, with low pH characteristics, high concentrations of sulfate and metals. The use of constructed wetlands (CWs) in the treatment of AMD is considered the most widely used technology among passive systems. The application of alternative by-products as a means of support for the system aims to reduce costs, correctly dispose of waste and has the advantage of reducing the exploitation of natural resources. In this sense, the objective of this work was to evaluate the performance of a wetland built with vertical flow in the treatment of acid mine drainage, using different types of support media. Three CW units were built, using different support media, the first filled with limestone gravel (CW1), the second with pulp industry waste (CW2) and the third with civil construction waste (CW3). In the upper part of the three units, there was a mixture of corn cob (SB) with cattle manure (EB), as a carbon source, aiming at reducing sulfate and metal precipitation. The experimental design was in units repeated in time. The macrophyte used was Thypha angustifolia, popularly known as Taboa. The systems were fed daily with a synthetic acid mine drainage effluent in four phases, with different concentrations and volumes. At the start, the systems were fed with water, without the presence of contaminants for the development of macrophytes, and then the application of the AMD began. The effluent was sampled and analyzed daily for pH, electrical conductivity, SO4-2, Cu, Zn, Mn and Fe concentrations. The COD analysis took place weekly. With this, the treatment of the DAM by the units and adequacy of the effluent by CONAMA Resolution 430 of 2011 was verified. Based on the results, WC2 presented a removal percentage of 86% to 97% of zinc, 77% to 97% of iron and 84% to 99% of manganese. However, for copper, the unit presented a limitation with a percentage in the first phase of 74% and decreasing in the last phase to 49%. WC3, on the other hand, showed the highest copper removal efficiency, with an average percentage of removal between 89% and 99%. For the other metals, the variation in the percentage of removal from the first phase to the last was from 75% to 32% in zinc, 8% to 96% in iron and 69 to 24% in manganese. In WC1 this percentage of removal varied from the first phase to the last from 88 to 70% in copper, 74% to 28% in zinc, -71% to 94% in iron and 73% to 33% in manganese. Residues from the cellulose industry and civil construction were effective in neutralizing the pH of the DAM. The average pH value in the four phases in WC2 ranged from 7.4 to 7.8 and in WC3 from 5.8 to 6.0. WC1 was the unit that presented the lowest pH value with an average value in the phases between 4.9 to 5.4. At no time were the units able to carry out the reduction of sulfate to sulfide, due to the wetland environment with an oxidizing characteristic. The wetland built with dregs and grits (CW2) showed greater efficiency in the removal of zinc, iron and manganese compared to the wetlands with limestone gravel (CW1) and construction waste (CW3). Alternative materials as a support medium for wetlands are promising in the treatment of acid mine drainage. WC2 proved to be the most recommended unit for the treatment of AMD, with a more acidic pH and presence of iron, zinc and manganese. While the effluent with copper concentration, WC3 is more recommended.